2019
DOI: 10.1002/cncr.32335
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation in adults with relapsed/refractory acute lymphoblastic leukemia who are treated with blinatumomab from a phase 3 study

Abstract: Background Blinatumomab, a bispecific T‐cell‐engaging (BiTE®) immuno‐oncology therapy, demonstrated superior overall survival versus standard‐of‐care chemotherapy (SOC) in adults with relapsed/refractory B‐cell precursor acute lymphoblastic leukemia (R/R ALL) in the phase 3 TOWER study. Herein, the authors reported clinical features and outcomes for those patients who underwent allogeneic hematopoietic stem cell transplantation (HSCT) after treatment with blinatumomab. Methods In the TOWER study, adults with R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(24 citation statements)
references
References 26 publications
3
21
0
Order By: Relevance
“…[23][24][25] This to bridge to HSCT or to reduce relapse after HSCT. 26,27 Therefore, currently, for patients who have failed to achieve CR with chemotherapy, we would administer some immunotherapy to reduce the leukemic burden as much as possible to the minimal residual disease-negative level so that we could expect to improve the outcome. However, immunotherapy may make the patient's condition more difficult to manage once they become resistant to this form of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] This to bridge to HSCT or to reduce relapse after HSCT. 26,27 Therefore, currently, for patients who have failed to achieve CR with chemotherapy, we would administer some immunotherapy to reduce the leukemic burden as much as possible to the minimal residual disease-negative level so that we could expect to improve the outcome. However, immunotherapy may make the patient's condition more difficult to manage once they become resistant to this form of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Blinatumomab, beneficial for OS in first or later salvage, was particularly effective in first salvage, where it more than doubled median survival relative to chemotherapy [51]. Salvage status drove survival in responders regardless of subsequent allogeneic stem cell transplantation [52]. Blinatumomab also provided clinically meaningful benefits in health-related quality of life [53].…”
Section: Adults With R/r Bcp-allmentioning
confidence: 99%
“…However, it also shows significant relapse rates. In a study in patients with R/R ALL who underwent allogenic HSCT after treatment with blinatumomab, it was found that transplantation reduced the risk of death by 55% and 46% in blinatumomab and SOC groups, respectively [52]. The best outcomes were in patients with no prior salvage therapy and MRD responses to blinatumomab regardless of on-study HSCT status [52].…”
Section: Health Economics and Outcomes Of Cd19 Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Blinatumomab prolonged OS with a median OS of 7.7 months versus 4.0 months for SOC, respectively. Patients achieving CR, CRh, or CRi after therapy with blinatumomab reportedly achieved durable responses and promising OS rates with or without subsequent HSCT [4]. Due to study limitations it is currently unclear whether patients responding to blinatumomab and obtaining MRD-negativity should undergo HSCT.…”
Section: Introductionmentioning
confidence: 99%